2018
DOI: 10.3390/foods7020013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bacteria, Probiotics and Diet in Irritable Bowel Syndrome

Abstract: Irritable bowel syndrome is a highly prevalent gastrointestinal disorder that threatens the quality of life of millions and poses a substantial financial burden on healthcare systems around the world. Intense research into the human microbiome has led to fascinating discoveries which directly and indirectly implicate the diversity and function of this occult organ in irritable bowel syndrome (IBS) pathophysiology. The benefit of manipulating the gastrointestinal microbiota with diet and probiotics to improve s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 125 publications
(138 reference statements)
0
36
0
5
Order By: Relevance
“…Indeed, a careful history may reveal patterns of symptoms linked to specific food consumption. Although debatable, a high-fiber diet has traditionally been encouraged particularly in IBS-C patients, given the absence of serious side effects and its potential benefit [88,89]. In recent years, there has been a growing clinical and scientific interest in the use of a diet low in FODMAPs (fermentable oligosaccharides, disaccharides, monosaccharides, and polyols) in IBS patients.…”
Section: Dietary Interventionmentioning
confidence: 99%
“…Indeed, a careful history may reveal patterns of symptoms linked to specific food consumption. Although debatable, a high-fiber diet has traditionally been encouraged particularly in IBS-C patients, given the absence of serious side effects and its potential benefit [88,89]. In recent years, there has been a growing clinical and scientific interest in the use of a diet low in FODMAPs (fermentable oligosaccharides, disaccharides, monosaccharides, and polyols) in IBS patients.…”
Section: Dietary Interventionmentioning
confidence: 99%
“…Antibiotics are a risk factor for IBS in asymptomatic individuals. Possible mechanisms should be investigated in future studies" [13] .…”
Section: Small Intestinal Bacterial Overgrowth and Ibsmentioning
confidence: 99%
“…IBS is narrowly defined by recurrent abdominal pain and discomfort associated with altered bowel habits in the absence of an organic origin or other explanation of symptoms 25 . This condition has a pooled global prevalence as high as 11.2% 26 but makes up as much as 60% of functional gastrointestinal disorders in children 27 . In 2016, the Rome Criteria IV was updated to include the following items to make a diagnosis of IBS: abdominal pain at least 4 days/month in the past 2 months with one or more of the following characteristics related to the abdominal pain: (1) relation to defecation, (2) a change in the frequency of stool, and (3) a change in the appearance of stool, as outlined in Table 1 28 .…”
Section: Ibsmentioning
confidence: 99%
“…A meta-analysis by Harper et al (2018) found that multistrain probiotic trials reported finding a clinically significant improvement in the quality of life of patients with IBS 27 . However, a randomized clinical trial with Hod et al (2016) found that an 8-week treatment with probiotics resulted in improved symptoms in women with IBS, but not significant compared to placebo 64 .…”
Section: Management Of Disaccharidase Deficiency In Ibsmentioning
confidence: 99%